1936 Ala. Laws 52 - (:unkn) unknown (My University, 1936)
No. 82, § 8: Prohibited transfer of a pistol to any person under the age of eighteen, to those believed to be convicted of a violent crime, drug addicts, habitual drunks, or those of unsound mind.
Keywords: TRANSFER - DANGEROUS PERSONS; TRANSFER - MINORS